Pertanggungjawaban Hukum Koperasi Yang Melakukan Pengelolaan Dana Anggota Secara Illegal - Kana Kurnia; Reza Hadrian (Jurnal de jure, 2024)
This case began when in 2019 KSP Indosurya did not submit financial reports and the annual member meeting in 2019 and in 2020 a number of customers experienced defaults. KSP Indosurya's mode is to promise high interest rates, namely as much as 9-12% per year , while conventional bank interest is only around 5-7% per year. This paper examines how the legal protection of members of savings and loan cooperatives according to law number 25 of 1992 concerning cooperatives, how is the legal responsibility of savings and loan cooperatives that collect and manage public funds illegally according to law number 25 of 1992 concerning cooperatives and how supervision government towards savings and loan cooperatives according to law number 1 of 2013 concerning microfinance institutions and law number 25 of 1992 concerning cooperatives. This research is a normative research using secondary data in the form of laws and regulations. The results of this study are first, there is no comprehensive legal protection for members, there are only preventive measures so that cooperative members can be more careful. Second, administrators can be personally responsible for returning cooperative members' funds if the cooperative's assets are not sufficient to fulfill its obligations. Third, referring to the principle of lex specialis derogate legi generalis, supervision of cooperative legal entities should be carried out by the Financial Services Authority, because in general the OJK has the authority to do so. To realize the effectiveness of legal protection, the authors suggest revising Law Number 25 of 1992 concerning Cooperatives by strengthening supervision and imposing sanctions from the Ministry of Cooperatives and Small and Medium Enterprises.